MENGEJAR KETERTINGGALAN: MENGGALI POTENSI SEKTOR AGRIBISNIS KABUPATEN FAKFAK, PROVINSI PAPUA BARAT - Pandhu Yuanjaya (NATAPRAJA, 2018)
This study aims to discuss policies in the agribusiness sector that was carried out by the Fakfak Regency government. This becomes important considering various policies in improving people's welfare was unsuccessful. Special autonomy which is expected to accelerate the pace of development has made the dependence on central government funding was increasing. This study used a qualitative approach.. The results of the study showed that the Fakfak Regency has large natural resource potential in the business sector. Policies that have been implemented the Agropolitan, Agro-tourism and Forest Management program. That policies trigger significant progress in productivity. The policies faced some challenges that is the availability of labor, the mindset of the community, customary land rights, investment, banking, cooperatives and the lack of performance of institutional networks (public, private and civil society partnerships).